Electrochemiluminescence-based detection method of lead(ii) ion via dual enhancement of intermolecular and intramolecular co-reaction. Issue 12 (21st June 2015) - Deng, Wei; Hong, Lin-Ru; Zhao, Min; Zhuo, Ying; Gao, Ming
<x xml:space="preserve">Abstract</x> An electrochemiluminescence sensor for highly selective and sensitive detection of lead(ii) ions (Pb2+) was developed taking advantage of the high specificity of the aptamer for Pb2+ and the use of both intermolecular and intramolecular co-reaction to achieve signal enhancement.